Photonuclear transmutation doping of the n-type detector silicon - Bochek, G.L.; Kulibaba, V.I.; Maslov, N.I.; Ovchinnik, V.D.; Potin, S.M.; Ryabka, P.M. (Вопросы атомной науки и техники, 2002)
New experimental quantitative data on the efficiency of photonuclear transmutation doping of n-type detector silicon were obtained. The express technique for measurement of the efficiency of producing the acceptor minority (Al) in high resistant detector silicon was developed. The transmutation doping is studied for increase of the detector silicon resistivity from about 1 to 5 kOhm x cm and for correction of the resistivity distribution over the silicon bulk. The studies of photonuclear doping were performed applying the beams of gamma-bremsstrahlung with Egmax ~ 25 MeV. Using the doping efficiency data, the cost of detector silicon doping was calculated for case of the bremsstrahlung of 25 MeV energy electrons.